2012
DOI: 10.1364/ol.37.001949
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber Fabry–Perot microresonator for nonlinear optics and cavity quantum electrodynamics

Abstract: We experimentally realize a Fabry-Perot-type optical microresonator near the cesium D2 line wavelength based on a tapered optical fiber, equipped with two fiber Bragg gratings that enclose a subwavelength diameter waist. Owing to the very low taper losses, the finesse of the resonator reaches F=86 while the on-resonance transmission is T=11%. The characteristics of our resonator fulfill the requirements of nonlinear optics and cavity quantum electrodynamics in the strong coupling regime. These characteristics,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 20 publications
0
63
0
Order By: Relevance
“…18 Wuttke et al reported the construction of a Fabry-P erot type optical microresonator on a tapered ONF by linking two normal fiber Bragg grating mirrors. 19 Similarly, Kato and Aoki experimentally observed strong coupling between single atoms and a moderate-finesse cavity in an all-fiber cavity system. 20 A nanofiber Bragg grating cavity can also be made directly using a focused ion beam (FIB) technique, which can modify or mill the fiber surface with nanometer precision.…”
mentioning
confidence: 87%
“…18 Wuttke et al reported the construction of a Fabry-P erot type optical microresonator on a tapered ONF by linking two normal fiber Bragg grating mirrors. 19 Similarly, Kato and Aoki experimentally observed strong coupling between single atoms and a moderate-finesse cavity in an all-fiber cavity system. 20 A nanofiber Bragg grating cavity can also be made directly using a focused ion beam (FIB) technique, which can modify or mill the fiber surface with nanometer precision.…”
mentioning
confidence: 87%
“…13,14 and approaching unity when combined with Bragg-grating cavities 15,16 . Until now, evanescent coupling of fluorescence photons to a single guided mode of a TOF has been achieved for a) email: lars.liebermeister@physik.uni-muenchen.de b) email: markusweber@lmu.de various solid state quantum emitters 17-20 , molecules 21 , and laser-cooled atomic vapors 22 .…”
mentioning
confidence: 99%
“…The tight confinement of light around ONFs Le , unique geometries provided by the fiber modes ; Reitz and Rauschenbeutel. (2012), low loss, and promise of improved atom-light interaction Alton et al (2011);Le Kien et al (2005b); ; Goban et al (2012); Wuttke et al (2012) have led to increased interest in the physics community. Optical micro-or nanofibers are used for sensing and detection Knight et al (1997); Nayak et al (2007), and coupling light to resonators Knight et al (1997); Kakarantzas et al (2002); Spillane et al (2003); Louyer et al (2005); Morrissey et al (2009);Fujiwara et al (2012), NV centers Schröder et al (2012), or photonic crystals Thompson et al (2013); Sadgrove et al (2013).…”
Section: Optical Nanofibers As Enablers Of High Cooperativity and Optmentioning
confidence: 99%
“…Wuttke et al (2012); Kato and Aoki (2015) use an optical fiber with printed Bragg reflectors and taper it with the flame-brushing technique to integrate an ONF inside an in-fiber optical cavity. Figure 20 shows the observation of vacuum Rabi splitting in this platform using a single trapped Cs atom in a state insensitive trap.…”
Section: Bragg Resonatorsmentioning
confidence: 99%